A Mindfulness-Based Intervention for University Students: A Feasibility Study - Christyn Dolbier; Lauren Conder; William Guiler; Erin Haley (The Ohio State University Libraries, 2022)
Background: Koru is a 4-week group mindfulness-based intervention that previously demonstrated psychological benefits in university students through its offering via a counseling center (Greeson, Juberg, Mayatan, James, & Rogers, 2014). Aim: This study examined the feasibility of Koru offered universally to students via collaborative outreach (i.e., student interest, attendance, adverse events, participant acceptability, and participant willingness to complete assessments). Method: Across five semesters, Koru was advertised via flyers, emails to student organizations and faculty and staff, and counseling center referrals at a southeastern public university with 29,000-students. Interested students were randomly assigned to Koru or a waitlist. In-person Koru groups took place in classrooms on campus. Assessments included practice logs, program evaluations, and pre- and post-intervention surveys measuring mindfulness and psychological symptoms. Results: Interest was sufficient to offer 2-3 groups per semester (171 students). Of those assigned to Koru, 44.4% completed 3-4 sessions and 34.9% did not attend any sessions. The adverse event rate was 2.9%. Evaluations were positive and all participants attending the last session completed them. The response rate was 29.0% for log completion and 17.9% for survey completion. Conclusion: Results support student interest in, and acceptability of Koru offered to all students on campus outside of a counseling center. Data collection was challenging.